Educational Service Quality Management as a Strategy to Increase School Competitiveness in the Era of Globalization - Anggra Prima; Nurlaili; Mulawarman, Widyatmke Gede; Yahya, Masrur (Journal of Educational Management Research, 2025)
This study aims to describe educational service quality management implementation, analyze strategies to improve school competitiveness through an educational service quality management approach, and offer applicable strategic recommendations based on quality management principles at State Senior High School 1 North Sangatta. This study uses a descriptive qualitative approach with the State Senior High School 1 North Sangatta research location. The research subjects included the principal, vice principal for curriculum and student affairs, education personnel, teachers, and several students and parents as users of educational services. Data was collected through observation, in-depth interviews, and documentation studies. Data analysis followed the interactive analysis model from Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions and verification. The study results indicate that quality management practices in schools have been implemented through several separate initiatives that reflect the reliability of academic services. However, there are still weaknesses in responsiveness, especially in administrative services and complaint systems. This study recommends strengthening an integrated quality management system based on information technology and strategic leadership to improve school competitiveness in the era of globalization.